ANALISIS PERSEPSI KONSUMEN TERHADAP KUALITAS LAYANAN DAN KEPUASAN KONSUMEN DI RESTORAN IKAN BAKAR MBAK TIN PURWOREJO - Andri Nurtantiono; Sektiyaningsih (JURNAL ILMIAH EDUNOMIKA, 2026)
This study analyzes consumer perceptions of service quality and satisfaction at the Mbak Tin Grilled Fish Restaurant in Purworejo using a descriptive qualitative research method through a questionnaire completed by 106 respondents. The study demonstrates the measurement of service quality using five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that tangibles have the greatest impact on customer satisfaction, despite all service quality components producing positive results. Furthermore, the dimensions of customer satisfaction also received positive ratings from respondents, including price appropriateness, intention to revisit, and willingness to recommend the restaurant. High customer satisfaction, indicated by good service, encourages customers to return and recommend the restaurant to others. The findings of this study have implications for restaurants in their efforts to improve service quality and maintain customer interest amidst intense competition in the culinary industry. Keywords: Customer Satisfaction, Service Quality